THE LINGUISTIC EVOLUTION OF IDENTITY: A COMPARATIVE STUDY OF LANGUAGE, GENDER, AND CULTURAL EXPRESSION IN MULTILINGUAL SOCIETIES - Dr. Samir Said (Modern American Journals, 2025)
Language is a fundamental tool for expressing and shaping identity in multilingual societies. The interaction between language, gender, and cultural expression plays a central role in the evolution of individual and collective identities. This paper explores how multilingualism influences identity formation, with particular emphasis on gender dynamics and cultural expression in societies where multiple languages coexist. By comparing case studies from diverse multilingual regions, this study investigates the ways in which language functions as both a reflection and a constitutive force in shaping gender roles, social norms, and cultural practices. It explores how the evolution of language within these societies contributes to the construction of identity, emphasizing the interplay between linguistic practices, gendered communication, and cultural identity in shaping social and political structures. Ultimately, this paper offers insights into how multilingualism can both preserve and transform societal identities.
Keywords: Linguistic Evolution, Identity, Gender, Multilingualism, Cultural Expression, Sociolinguistics, Language and Gender, Identity Formation, Multiculturalism, Social Identity.